ANALYSIS OF THE IMAGE OF A WOMAN IN JAVLON JOVLIYEV'S STORY - Aktamova Go'zal, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes the image of a woman in Uzbek literature based on Javlon Jovliyev's story "Woman". The article covers the social and psychological aspects of the image of a woman. In particular, the role and status of a woman in society, the evolution of a woman's soul despite various inequalities are analyzed.